Improving the Ability of Mastering Indonesian Vocabulary through Unjumble Media in Writing Learning for Grade 2 Students (LITPAM, 2025)
Vocabulary mastery is key in developing good and correct writing skills. However, based on field observations, elementary school students in Bengkel Village, Buleleng, tend to be more accustomed to using their mother tongue, namely Balinese, both in everyday life and in the learning environment. This condition hampers their ability to write Indonesian effectively. The study aims to analyze and determine the increase in the ability to master Indonesian vocabulary through Unjumble media in writing learning for grade 2 students of SDN 3 Bengkel. The research method uses the One-Group Pre-Test and Post-Test Design. The research sample was 20 grade 2 students of SDN 3 Bengkel . The feasibility of the media was carried out through teacher and student response questionnaires to the media. Data analysis using quantitative analysis N-Gain calculation and qualitative analysis. The results of the study stated that pre-test and post-test results of students with an average pre-test score of 58.54 and increased in the post-test to 89.26. The percentage of student learning completion also increased in the pre-test stage with a percentage of 25% increasing to 100% in the post-test stage. The percentage of student activity increased from 40% in the pre-test stage to 95% in the post-test stage. The increase in activity occurred after the Unjumble learning media was applied. The calculation results using the N-Gain formula showed a value of 0.74 or a High category. The results of the media validity based on the teacher response questionnaire obtained a percentage of 95% with a Very Appropriate category. The results of the questionnaire showed that the overall percentage of student questionnaire answers obtained a result of 85% or fell into the Very Appropriate and Very Practical categories.